Students' Independent Learning Strategies in Understanding and Developing Learning Materials They Have Received at School at SMPN 6 Mataram - Toriq Aziz; Baiq Syakila Dwi Satria; Igatun Haniah; Hani Amelia Putri; Fiqri’ah; Baiq Syiva Hulida Aulia; Edy Herianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to identify Students' Independent Learning Strategies in Understanding and Developing Subject Matter that has been obtained at School at SMPN 6 Mataram. This study uses a qualitative descriptive method with data collection through interviews, observations, and documentation. The subjects of the study involved students of SMPN 6 Mataram who have various learning preferences. The results of the study indicate that Students' Independent Learning Strategies consist of: (1) Identification of effective independent learning methods for students, (2) The influence of motivation and discipline on the success of independent learning, (3) Utilization of technology-based learning media to support understanding of the material, (4) Obstacles faced by students in implementing independent learning strategies, and (5) The role of teacher guidance in helping students determine appropriate learning strategies. This study provides insight into the importance of independent learning as an effort to improve students' understanding of subject matter and prepare them to become lifelong learners.